1981
DOI: 10.1104/pp.67.6.1069
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thylakoid Membrane Fluidity and the Functioning of Pea Chloroplasts

Abstract: Cholesteryl hemisuccinate has been incorporated into pea chloroplast thylakoids to investigate the relationship between fluidity and functioning of this membrane system. Levels of sterol which increased the apparent viscosity of the membrane, estimated by fluorescence polarization measurements using the lppboilic probe, 1,6-diphenyl-1,3,5 hexatriene, affected several photosynthetic processes. A decrease in fluidity was accompanied by an inhibition of dark limiting steps associated with electron transfer betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…After incubation, the membranes were washed two times in order to remove the non-incorporated sterol and resuspended in a medium appropriate for further measurements. Alternatively, the method of Yamamoto et al (1981) to incorporate cholesterol by the use of polyvinyl pyrrolidone as a mediator was checked. Fluorescence polarization (P) of 1,6-diphenyl-1, 3, 5-hexatriene (DPH) indicates that with both methods, the level of cholesterol incorporation is approximately the same.…”
Section: Incorporation Of Sterolsmentioning
confidence: 99%
“…After incubation, the membranes were washed two times in order to remove the non-incorporated sterol and resuspended in a medium appropriate for further measurements. Alternatively, the method of Yamamoto et al (1981) to incorporate cholesterol by the use of polyvinyl pyrrolidone as a mediator was checked. Fluorescence polarization (P) of 1,6-diphenyl-1, 3, 5-hexatriene (DPH) indicates that with both methods, the level of cholesterol incorporation is approximately the same.…”
Section: Incorporation Of Sterolsmentioning
confidence: 99%
“…Several studies on this topic that use thylakoid membranes with artificially manipulated lipid phase (incorporation of cholesterol or cholesteryl hemisuccinate) or lipid mutants (genetically altered membrane fluidity) discuss the importance of fluidity of the lipid matrix on functional characteristics of the photosynthetic apparatus, located in thylakoid memAbbreviations: 1,4 BQ, 1,4-benzoquinone; chl, chlorophyll; DCMU, 3-(3,4-dichlorophenyl)-1,1-dimethylurea; DCPIP, 2,6-dichlorophenolindophenol; DPH, 1,6-diphenyl-1,3,5-hexatriene; DPPC, dipalmitoylphosphatidylcholine; MES, 2-(morpholino)ethanesulfonic acid; MV, methyl viologen; PSI (II), photosystem I (II); TMA-DPH, trimethylammonium-diphenyl-DPH; Tricine, N-[tris(hydroxymethyl) (Ford and Barber, 1983;Siegenthaler and Tremolieres, 1998;Yamamoto et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Mg2' to the low-salt suspension of control chloroplasts induced an increase in the yield ofChl a fluorescence as reported for several other systems by a number of workers (4,18). However, the Mg2+-induced increase in the room temperature Chl a fluorescence was either absent or significantly diminished in thylakoid membranes isolated from plants grown in the presence of BASF 13.338.…”
mentioning
confidence: 69%
“…Barber et al (4) suggested that the cation-induced increase in Chl a fluorescence can be used as an intrinsic probe for monitoring changes in the fluidity of the thylakoid membranes. Direct experimental evidence in support of this suggestion is derived from the correlation between cation-induced fluorescence changes and polarization of diphenyl hexatriene fluorescence in aging chloroplasts (4) as well as in thylakoid membranes infused with cholesteryl hemisuccinate (4,18).…”
mentioning
confidence: 77%